EVALUATING KERALA’S COMMITMENT TO RESPONSIBLE TOURISM: INSIGHTS FROM DOMESTIC TOURISTS - Baral, Ankit; Rahman, Faslu; Ariyaputhiri, Sadanandam (Palash: A Journal of Hospitality and Tourism Service Management, 2025)
Kerala, renowned as ‘God’s Own Country,’ has emerged  as a leader in India’s responsible tourism sector, attracting  21.8 million domestic tourists in 2023 through its unique  offerings in cultural, wellness, and rural tourism experiences.  This study examines domestic tourists’ perceptions of  Kerala’s responsible tourism initiatives, with four specific  objectives: (1) To analyze socio-economic and tripographic  profiles of visitors, (2) To assess how demographic factors  influence satisfaction levels, (3) To evaluate the alignment  between expectations and actual experiences, and (4) To  identify critical gaps in responsible tourism offerings.  Using a quantitative approach, data was collected through a  structured questionnaire administered to domestic tourists,  incorporating both tripographic details and Likert-scale  responses. The analysis employed descriptive statistics,  paired sample t-tests, and one-way ANOVA to process the  survey results. Findings reveal that while tourists show  overall satisfaction with cultural and festival tourism (with  78% expressing revisit intention), significant expectation satisfaction gaps exist in wellness tourism (particularly Ayurveda services) and rural infrastructure.  The study highlights the need for standardized  service quality and enhanced rural connectivity  to strengthen Kerala’s position as a sustainable  tourism destination, offering actionable insights  for policymakers and industry stakeholders  to optimize the state’s responsible tourism  framework
Keywords: Tourism; Sustainable development; Domestic tourist; Expectation; Satisfaction